A method and material for growing perovskite on a van der waals surface heteroepitaxy

CN122918700APending Publication Date: 2026-10-16SUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611209708.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0007]针对现有机械剥离与转移技术制备如二维铁电钙钛矿等钙钛矿异质结时存在的界面有机污染、晶格取向高度随机以及由此引发的界面态缺陷和铁电极化退化等问题,本发明提供一种在范德华表面异质外延生长钙钛矿的方法及材料,将反胶束工程化设计为界面传输载体,以克服润湿势垒,实现在范德华衬底上直接原位异质外延生长二维铁电钙钛矿等钙钛矿材料

Benefits of technology

[0023] Compared with the prior art, the beneficial effects of the present invention are at least as follows:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918700A_ABST
    Figure CN122918700A_ABST
Patent Text Reader

Abstract

The application relates to a method for growing a perovskite on a van der Waals surface by using a reverse micelle solution and a material, the method comprising the following steps: dissolving a perovskite material in a strong polar and coordination solvent to prepare a precursor solution, wherein the perovskite material is a two-dimensional ferroelectric perovskite, a two-dimensional non-ferroelectric organic-inorganic hybrid perovskite or an inorganic lead-free perovskite; mixing the precursor solution, a surfactant and a non-polar or weakly polar organic solvent which is affinity to the non-polar end of the surfactant, and obtaining a reverse micelle solution by taking supernatant after centrifugation; dropping the reverse micelle solution on a van der Waals substrate and standing and heating until completely dried to obtain the material; the reverse micelle is designed as an interface transmission carrier to overcome the wetting barrier, so that the two-dimensional ferroelectric perovskite and other perovskite materials can be directly and in-situ hetero-epitaxially grown on the van der Waals substrate, and the perovskite material can be used as a ferroelectric material and a photoelectric material, thereby providing a basis for the development of high-performance ultrathin ferroelectric devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional materials technology, specifically relating to a method and materials for epitaxial growth of perovskite on van der Waals surfaces using a reverse micelle solution. Background Technology

[0002] Perovskite materials, with their excellent optical and electrical properties, have shown great potential for application in many fields. For example, ferroelectric materials, as functional materials, are a crucial foundation for next-generation micro- and nano-devices such as sensing, non-volatile storage, and data-intensive computing. However, the realization of ultrathin ferroelectric systems is fundamentally limited by the depolarization field. As the film thickness decreases, the depolarization field increases dramatically, disrupting the spontaneous polarization stability of traditional bulk ferroelectrics. Against this backdrop, two-dimensional van der Waals heterostructures provide a unique synthetic framework for engineered polar interfaces. By combining nonpolar van der Waals materials with structurally or chemically asymmetric layers, interfacial symmetry breaking and charge redistribution can be introduced. In such systems, polarization is controlled by atomic arrangement and interlayer coupling, thereby avoiding depolarization instability. Meanwhile, perovskites such as two-dimensional ferroelectric perovskites have inherent lattice flexibility and chemical tunability, making them ideal solution-processing building blocks for realizing ultrathin polar materials. Therefore, heteroepitaxial integration of two-dimensional ferroelectric perovskites with van der Waals substrates such as molybdenum disulfide is a key path to constructing a new generation of high-performance ultrathin ferroelectric devices.

[0003] Currently, the mainstream and relatively mature existing technology for preparing two-dimensional ferroelectric perovskite-MoS2 heterojunctions is the "mechanical exfoliation and transfer technique." The specific steps of this technique are as follows: A few layers or a single layer of two-dimensional flakes are exfoliated from a two-dimensional layered perovskite single-crystal bulk or a MoS2 bulk crystal using mechanical exfoliation. The exfoliated flakes are then attached to an intermediate polymer carrier. With the aid of a micromanipulation stage and an optical microscope, the polymer carrier carrying the perovskite flakes is moved above a target substrate pre-placed with MoS2 for alignment. Subsequently, the perovskite is released and bonded to the MoS2 through mechanical imprinting, heating above the polymer's glass transition temperature, or dissolving the polymer carrier with organic solvents such as acetone, thereby obtaining the heterojunction. Although the mechanical exfoliation and transfer technique is widely used in laboratory-level preliminary verification of device physical mechanisms, it still suffers from the following significant and difficult-to-overcome physical defects in interface physical mechanism research and practical applications:

[0004] I. Interface Contamination and Defect State Introduction Weaken Ferroelectric Coupling: In the mechanical transfer process, the reliance on polymers such as PDMS or PMMA as intermediate media is unavoidable. The cleaning with organic solvents and the pyrolysis or dissolution of the polymers easily leave organic hydrocarbon residues at the physical interface of the heterojunction. Furthermore, during physical bonding in an atmospheric environment, air and water oxygen molecules are easily trapped at the interface, forming nanoscale bubbles. These interface impurities and pores act as numerous carrier trapping and scattering centers in the heterojunction, significantly increasing the interface contact resistance and hindering effective carrier injection and the effective control of the MoS2 channel by the ferroelectric polarization field.

[0005] Second, random lattice orientation and lack of epitaxial matching: Mechanical transfer is essentially a macroscopic physical splicing process. The in-plane stacking twist angle between two two-dimensional crystal layers has extremely high randomness. This disordered splicing cannot achieve atomic-level lattice matching at the interface, resulting in the heterojunction interface being in a high-energy metastable state. For ferroelectric perovskite materials that are highly dependent on lattice stress and structural symmetry, interface lattice mismatch will induce polarization degradation, leading to a decrease in the stability of the ferroelectric phase. This manifests macroscopically as insufficient ferroelectric polarization retention force and severe ferroelectric fatigue in heterojunction devices.

[0006] Third, the thickness and morphology are uncontrollable, making large-scale fabrication impossible: Due to differences in cleavage energy and random stress distribution, the perovskite sheets obtained by mechanical exfoliation are uncontrollable in terms of lateral dimensions, thickness uniformity, and geometric morphology. This inhomogeneity and randomness mean that this method can only be used to prepare isolated, randomly distributed micron-sized samples, fundamentally excluding its application to large-area, arrayed, high-quality ferroelectric heterostructure epitaxial integration. Summary of the Invention

[0007] To address the problems of interfacial organic contamination, highly random lattice orientation, and resulting interfacial state defects and ferroelectric polarization degradation in the preparation of perovskite heterostructures such as two-dimensional ferroelectric perovskites using existing mechanical exfoliation and transfer techniques, this invention provides a method and materials for heteroepitaxial growth of perovskites on van der Waals surfaces. The reverse micelles are engineered as interfacial transport carriers to overcome the wetting barrier, enabling direct in-situ heteroepitaxial growth of two-dimensional ferroelectric perovskite and other perovskite materials on van der Waals substrates.

[0008] The technical solution adopted by this invention to solve its technical problem is:

[0009] A first aspect of the present invention is to provide a method for heteroepitaxial growth of perovskite on a van der Waals surface, the method comprising:

[0010] Step 1: Dissolve the perovskite material in a strongly polar solvent with coordination ability to prepare a precursor solution. The perovskite material is a two-dimensional ferroelectric perovskite, a two-dimensional non-ferroelectric organic-inorganic hybrid perovskite, or an inorganic lead-free perovskite. Add a surfactant and a non-polar or weakly polar organic solvent that is affinity for the non-polar end of the surfactant to the precursor solution. After mixing evenly, a mixture is obtained. After centrifuging the mixture, the supernatant is collected to obtain a reverse micelle solution.

[0011] Step 2: Take the reverse micelle solution obtained in Step 1 and drop it onto the van der Waals substrate and let it stand. Then heat the van der Waals substrate with the reverse micelle solution until the reverse micelle solution is completely dry to obtain a material with perovskite heteroepitaxially grown on the van der Waals surface.

[0012] In the preferred technical solution, the two-dimensional ferroelectric perovskite is (DFCHA)2PbI4, the two-dimensional non-ferroelectric organic-inorganic hybrid perovskite is (PEA)2PbBr4 or (BA)2PbBr4, and the inorganic lead-free perovskite is Cs3Bi2Br9 or Cs3Sb2Br9.

[0013] In a preferred embodiment, the molar concentration of the perovskite material in the precursor solution is 0.02~0.1mol / L, and the volume ratio of the precursor solution, surfactant, and nonpolar or weakly polar organic solvent is 1:(10~30):10.

[0014] In a preferred embodiment, the highly polar solvent with coordination ability is one or more of N,N-dimethylformamide, dimethyl sulfoxide, γ-butyrolactone, and N-methylpyrrolidone.

[0015] In a preferred embodiment, the surfactant is an amphiphilic organic carboxylic acid having a single-terminal carboxyl group and an aliphatic hydrocarbon chain.

[0016] In a preferred embodiment, the amphiphilic organic carboxylic acid is butyric acid, valeric acid, hexanoic acid, or octanoic acid.

[0017] In a preferred embodiment, the nonpolar or weakly polar organic solvent is one or a mixture of chlorobenzene, toluene, xylene, chloroform, and n-hexane.

[0018] In a preferred embodiment, the van der Waals substrate is a SiO2 sheet with a single layer of MoS2.

[0019] In a preferred embodiment, the method further includes: dissolving a molybdenum source and an alkaline modifier in a solvent to prepare a MoS2 precursor solution; spin-coating the MoS2 precursor solution onto a SiO2 / Si substrate; and then annealing it with sulfur powder in an argon atmosphere to obtain a SiO2 wafer loaded with a monolayer of MoS2.

[0020] In the preferred technical solution, in step two, the heating temperature is controlled to be 100~140℃.

[0021] A second aspect of the present invention is to provide a material for heteroepitaxial growth of perovskite on a van der Waals surface, said material being manufactured by the method for heteroepitaxial growth of perovskite on a van der Waals surface as described in any one of the preceding claims.

[0022] The applications of the aforementioned materials for heteroepitaxial growth of perovskites on van der Waals surfaces include using the materials as ferroelectric materials and optoelectronic materials.

[0023] Compared with the prior art, the beneficial effects of the present invention are at least as follows:

[0024] I. This invention engineered the antimicelles as an interface transport carrier to overcome the wetting barrier and achieve direct in-situ heteroepitaxial growth of two-dimensional ferroelectric perovskite and other perovskite materials on van der Waals substrates. This results in a lattice-matched epitaxial interface free from interface contamination and defect introduction. Significant symmetry breaking is induced at the two-dimensional interface through heteroepitaxial growth, solving the problem of weakened ferroelectric coupling due to interface contamination and defect state introduction when preparing two-dimensional ferroelectric perovskite heterojunctions using existing mechanical exfoliation and transfer techniques. This mechanism successfully excites stable functional out-of-plane ferroelectricity with a 180° phase reversal in the (DFCHA)2PbI4 bulk material, which originally only has in-plane polarization characteristics.

[0025] Second, the electric dipoles generated by the redistribution of charges under the influence of an electric field undergo spring-like stretching and contraction vibrations, and the natural gaps between van der Waals layers provide space for electrical strain. For example, the (DFCHA)₂PbI₄ / MoS₂ epitaxial heterostructure exhibits out-of-plane piezoelectricity with an out-of-plane piezoelectric coefficient of 15 pm / V. This novel ferroelectric and piezoelectric property, stimulated by interface coupling with symmetry breaking, solves the problems caused by random lattice orientation and lack of epitaxial matching relationships in the preparation of two-dimensional ferroelectric perovskite heterostructures using existing mechanical exfoliation and transfer techniques. It surpasses the scaling limitations of traditional bulk ferroelectric materials and provides a foundation for the development of ultrathin non-volatile memory devices and high-performance ultrathin ferroelectric devices.

[0026] Third, this invention utilizes reverse micelle solutions and can also be applied to other perovskite materials such as two-dimensional nonferroelectric organic-inorganic hybrid perovskites or inorganic lead-free perovskites, achieving the same epitaxial effect. It solves the problems of uncontrollable thickness and morphology and inability to scale up preparation when using existing mechanical exfoliation and transfer technologies to prepare perovskite heterojunctions. It is suitable for large-area, array-based large-scale preparation and provides a feasible technical path for large-scale integrated applications in fields such as photodetectors, light-emitting diodes, and high-sensitivity X-ray detectors. Attached Figure Description

[0027] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which:

[0028] Figure 1 These are optical microscope images of the (DFCHA)2PbI4 / MoS2 epitaxial heterostructures in Examples 1-6 of the present invention; wherein a is an optical microscope image of Example 1; b is an optical microscope image of Example 2; c is an optical microscope image of Example 3; d is an optical microscope image of Example 4; e is an optical microscope image of Example 5; and f is an optical microscope image of Example 6.

[0029] Figure 2 The piezoelectric microscopy results of the phase hysteresis loop and amplitude butterfly curve of the (DFCHA)2PbI4 / MoS2 epitaxial heterostructure of this invention in the out-of-plane direction are shown.

[0030] Figure 3 This is an out-of-plane piezoelectric microscopy scan of the (DFCHA)2PbI4 / MoS2 epitaxial heterostructure of the present invention.

[0031] Figure 4 This is an optical microscope image of the (PEA)2PbBr4 / MoS2 epitaxial heterostructure in Example 7 of the present invention.

[0032] Figure 5 This is an optical microscope image of the (BA)2PbBr4 / MoS2 epitaxial heterostructure in Example 8 of this invention.

[0033] Figure 6 This is an optical microscope image of the Cs3Bi2Br9 / MoS2 epitaxial heterostructure in Example 9 of this invention.

[0034] Figure 7 This is an optical microscope image of the Cs3Sb2Br9 / MoS2 epitaxial heterostructure in Example 10 of the present invention.

[0035] Figure 8 This is an optical microscope photograph of the material in Comparative Example 1 of this invention.

[0036] Figure 9 These are optical microscope images of the materials in Comparative Example 2 of this invention.

[0037] Figure 10 These are optical microscope images of the materials in Comparative Example 3 of this invention.

[0038] Figure 11 These are optical microscope images of the materials in Comparative Example 4 of this invention.

[0039] Figure 12These are optical microscope images of the materials in Comparative Example 5 of this invention. Detailed Implementation

[0040] The embodiments of the present invention are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.

[0041] To address the problems of interfacial organic contamination, highly random lattice orientation, and resulting interfacial state defects and ferroelectric polarization degradation in the preparation of two-dimensional ferroelectric perovskite heterostructures using existing mechanical exfoliation and transfer techniques, the solution crystallization method, typically represented by spin coating, involves completely dissolving the solid powder or halide precursor required for the synthesis of two-dimensional perovskite in a highly polar organic solvent (such as N,N-dimethylformamide DMF or dimethyl sulfoxide DMSO) to prepare a polar precursor solution containing solvated complexes. This polar precursor solution is then spin-coated to forcibly spread into a uniform thin liquid film on the substrate surface. Following thermal annealing, as the highly polar solvent with coordinating ability gradually evaporates at high temperatures, the liquid film system reaches a supersaturated state, thereby driving spontaneous nucleation and crystal growth of the precursor solute on the substrate, ultimately yielding a macroscopic perovskite solid film. However, the inventors discovered during their research that:

[0042] In conventional solution systems, perovskite precursors typically exist as charge-asymmetric solvated complexes with strong intrinsic polarity. Conversely, van der Waals substrates such as molybdenum disulfide (MoS2) have charge-neutral surfaces without dangling bonds, making them typical nonpolar inert surfaces. This polarity difference leads to a lack of effective electrostatic adsorption or chemical interaction between the solution and the substrate. Due to the weak interfacial interactions, in conventional spin-coating, the strong intermolecular attraction within the solvated precursor dominates during solvent evaporation. This thermodynamic tendency drives the polar precursor to preferentially aggregate within the bulk solution (homogeneous nucleation) rather than undergo ordered adsorption on the target substrate surface (heterogeneous nucleation). The core of epitaxial growth lies in the kinetic guidance of the nucleation of the upper material by the atomic arrangement of the underlying substrate. Because conventional spin-coating causes the nucleation process to mainly occur within the solution rather than at the heterogeneous interface, the perovskite crystal cannot sense and conform to the lattice of the underlying MoS2. Therefore, the crystallized products can only be stacked on the substrate in a random sedimentation manner, forming a non-epitaxymatic film with disordered arrangement and random orientation.

[0043] To address the aforementioned problems, this invention proposes a method for van der Waals epitaxial growth of perovskite materials such as ferroelectric perovskite (DFCHA)2PbI4 (DFCHA = 4,4-difluorocyclohexylamine) on MoS2 using a reverse micelle solution. The reverse micelles are engineered as interfacial transport carriers to overcome the wetting barrier. A preferred embodiment of the method for heteroepitaxial growth of perovskite on a van der Waals surface described in this invention includes:

[0044] Step 1: Dissolve the perovskite material in a strongly polar solvent with coordination ability to prepare a precursor solution. The perovskite material is a two-dimensional ferroelectric perovskite, a two-dimensional non-ferroelectric organic-inorganic hybrid perovskite, or an inorganic lead-free perovskite. Add a surfactant and a non-polar or weakly polar organic solvent that is affinity for the non-polar end of the surfactant to the precursor solution. After mixing evenly, a mixture is obtained. After centrifuging the mixture, the supernatant is collected to obtain a reverse micelle solution.

[0045] Step 2: Take the reverse micelle solution obtained in Step 1 and drop it onto the van der Waals substrate and let it stand. Then heat the van der Waals substrate with the reverse micelle solution until the reverse micelle solution is completely dry to obtain a material with perovskite heteroepitaxially grown on the van der Waals surface.

[0046] The reverse micelle solution described above comprises a highly polar solvent with coordination ability, a surfactant, and a nonpolar or weakly polar organic solvent with affinity for the nonpolar end of the surfactant. The highly polar solvent with a certain coordination ability can dissolve the perovskite material and form coordination bonds with it, contributing to the stability of the polar core within the material. The surfactant enables the reverse micelles to anchor on the van der Waals substrate surface, breaking polar repulsion. The nonpolar or weakly polar organic solvent does not dissolve the precursor and can maintain the independent suspension of the reverse micelles in the liquid phase, preventing... To prevent premature breakage and homogeneous aggregation, these three solvents together form reverse micelles that can both complete the growth of perovskite crystals and transport substances to nonpolar van der Waals substrates. Then, in the liquid phase, the reverse micelle system containing surfactants is used to encapsulate the perovskite precursor and transport it to the nonpolar van der Waals surface, driving the heteroepitaxial growth of perovskite crystals. This results in a lattice-matched epitaxial interface without interface contamination and defect introduction, enabling the direct in-situ heteroepitaxial growth of perovskite materials such as ferroelectric perovskites on van der Waals substrates (such as MoS2).

[0047] In the preferred technical solution, the two-dimensional ferroelectric perovskite is (DFCHA)2PbI4, the two-dimensional non-ferroelectric organic-inorganic hybrid perovskite is (PEA)2PbBr4 or (BA)2PbBr4, and the inorganic lead-free perovskite is Cs3Bi2Br9 or Cs3Sb2Br9.

[0048] The above method can integrate various types of perovskites onto van der Waals surfaces. For example, when the two-dimensional ferroelectric perovskite is (PEA)2PbI4, the material can be used as a ferroelectric material to prepare ultrathin non-volatile memory devices; when the two-dimensional non-ferroelectric organic-inorganic hybrid perovskite is (PEA)2PbBr4 or (BA)2PbBr4, the material can be used to prepare photodetectors and light-emitting diodes; when the inorganic lead-free perovskite is Cs3Bi2Br9 or Cs3Sb2Br9, the material can be used to prepare green and environmentally friendly (lead-free) photodetectors and high-sensitivity X-ray detectors.

[0049] In a preferred embodiment, the molar concentration of the perovskite material in the precursor solution is 0.02~0.1mol / L, and the volume ratio of the precursor solution, surfactant, and nonpolar or weakly polar organic solvent is 1:(10~30):10.

[0050] For example, when the heating temperature in step two is kept at 120°C, the volume ratio of the precursor solution, surfactant, and non-polar or weakly polar organic solvent should be at least 1:10:10. If the amount added is less than this ratio, a perovskite layer with a thickness of nanometers cannot be epitaxially grown. The ratio of the three should be at most 1:30:10. If the ratio is exceeded, the perovskite cannot be grown due to insufficient content.

[0051] In a preferred embodiment, the highly polar solvent with coordination ability is one or more of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), γ-butyrolactone (GBL), and N-methylpyrrolidone (NMP) (such as a solvent in which DMF and DMSO are mixed in different volume ratios).

[0052] For example, the highly polar solvent with coordination ability is DMF. DMF has extremely high solubility for perovskite precursors (such as DFCHAI and PbI2), and its internal molecules can react with lead ions (Pb). 2+ The formation of appropriate Lewis acid-base coordination bonds helps stabilize the polar nucleus internally. DMF has a moderate boiling point (approximately 153°C), which provides a stable solvent evaporation rate when crystallized at a heating temperature of 120°C. This effectively avoids uncontrolled nucleation caused by instantaneous boiling (bumping) of the solvent, ensuring the orderly progress of epitaxial growth.

[0053] In a preferred embodiment, the surfactant is an amphiphilic organic carboxylic acid having a single-ended carboxyl group (hydrophilic end) and an aliphatic hydrocarbon chain (hydrophobic end).

[0054] For example, the amphiphilic organic carboxylic acid is butyric acid, valeric acid, hexanoic acid, or octanoic acid. The polar carboxyl end of organic carboxylic acids such as octanoic acid coordinates inward with the metal ion, while the nonpolar carbon chain end faces outward, so that the reverse micelles can be anchored to the MoS2 surface by London dispersion force, breaking the polar repulsion. In addition, by selecting carboxylic acids with different carbon chain lengths such as butyric acid, valeric acid, hexanoic acid, or octanoic acid, the steric hindrance and thermal annealing temperature of the reverse micelles can be adjusted.

[0055] In a preferred embodiment, the nonpolar or weakly polar organic solvent is one or more of chlorobenzene, toluene, xylene, chloroform, and n-hexane. For example, chlorobenzene acts as an antisolvent; it does not dissolve the precursor and can maintain the independent suspension of reverse micelles in the liquid phase, preventing premature rupture and homogeneous aggregation.

[0056] In a preferred embodiment, the van der Waals substrate is a SiO2 sheet with a single layer of MoS2; for example, ferroelectric perovskite is grown on MoS2 by van der Waals epitaxy using a reverse micelle solution.

[0057] In a preferred embodiment, the method further includes: dissolving a molybdenum source and an alkaline modifier in a solvent to prepare a MoS2 precursor solution; spin-coating the MoS2 precursor solution onto a SiO2 / Si substrate; and then annealing it with sulfur powder in an argon atmosphere to obtain a SiO2 sheet loaded with a monolayer of MoS2; for example, preparing triangular monolayer MoS2 nanosheets.

[0058] In the preferred technical solution, in step two, the heating temperature is controlled to be 100~140℃; for example, the heating temperature is 100℃, 120℃, 130℃, or 140℃; assuming the molar concentration of perovskite material in the precursor solution is 0.1mol / ml, and the volume ratio of the precursor solution, surfactant, and nonpolar or weakly polar organic solvent is 1:20:10, if the heating temperature is less than 100℃, it is difficult to destroy the reverse micelle structure, and the precursor cannot be released for epitaxial growth; if the heating temperature is greater than 140℃, the solvent evaporation rate is too fast, which will lead to uncontrolled nucleation, rapid precipitation of solute to form irregular crystals, and failure to complete epitaxial growth.

[0059] All pharmaceuticals and reagents used in the following examples and comparative examples were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0060] The preparation method of (DFCHA)₂PbI₄ in the following examples and comparative examples includes: reacting 4,4-difluorocyclohexylamine with an aqueous hydroiodic acid solution in anhydrous ethanol to synthesize 4,4-difluorocyclohexylamine iodide; subsequently, adding 2.0 mmol (0.52 g) of 4,4-difluorocyclohexylamine iodide, 1 mmol (0.46 g) of lead iodide and 10 mL of aqueous hydroiodic acid solution to a round-bottom flask and mixing, heating under reflux at 353 K for 4 hours to obtain a clear solution, and then evaporating and crystallizing the solution to produce orange-yellow (DFCHA)₂PbI₄ crystals.

[0061] The preparation method of SiO2 sheets loaded with monolayer MoS2 in the following examples and comparative examples includes: dissolving 0.12g of ammonium molybdate and 0.08g of KOH in 5mL of deionized water to prepare a MoS2 precursor solution; spin-coating the MoS2 precursor solution onto a SiO2 / Si substrate at a speed of 8000rpm for 30 seconds; and then placing the substrate and sulfur powder into a tube furnace and annealing at 720°C for 10 minutes under an argon atmosphere to finally obtain triangular monolayer MoS2 nanosheets.

[0062] The test conditions in the following examples and comparative examples were as follows: Macroscopic growth morphology and distribution of the epitaxial heterostructures were acquired under bright-field conditions using a Nikon ECLIPS ELV150N optical microscope. A commercial scanning probe microscope system (MFP-3D, Oxford Instruments) equipped with a conductive platinum / iridium (Pt / Ir) coated probe was used for testing. Polarization response testing employed Dual AC Resonance Tracking Scanning Extended Gradient Voltage Power Microscopy (DART-SS-PFM) mode. An AC driving voltage was applied at room temperature and with the DC bias off-field to record phase and amplitude signals.

[0063] Example 1: A method for heteroepitaxial growth of perovskite on van der Waals surfaces, the method comprising:

[0064] Step 1: Dissolve 9.79 mg (0.010 mmol) of (DFCHA)₂PbI₄ powder in 0.1 mL of N,N-dimethylformamide (DMF) solvent to prepare a precursor solution with a molar concentration of 0.1 mol / L. Take 0.01 mL of the precursor solution and add 0.2 mL of n-octanoic acid and 0.1 mL of chlorobenzene sequentially, and mix thoroughly. The volume ratio of precursor solution, n-octanoic acid, and chlorobenzene is 1:20:10. After mixing thoroughly, a mixture is obtained. Place the mixture in a centrifuge and centrifuge at 8000 rpm for 5 minutes. Collect the supernatant to obtain the reverse micelle solution.

[0065] Step 2: Take 0.02 mL of the reverse micelle solution obtained in Step 1 and drop it onto a van der Waals substrate. The van der Waals substrate is a SiO2 sheet with a monolayer of MoS2. After letting it stand for a short time, transfer the van der Waals substrate with the dropped reverse micelle solution onto a heating stage preheated to 120°C and heat until the reverse micelle solution is completely dry. This yields a material with heteroepitaxially grown perovskite on the van der Waals surface. An optical microscope image of the epitaxial heterostructure is attached. Figure 1 As shown in Figure a, two-dimensional ferroelectric perovskite (DFCHA)2PbI4 was successfully grown on triangular MoS2 nanosheets.

[0066] Compared to traditional mechanical peeling and transfer techniques, which rely on polymer media and suffer from hydrocarbon contamination, bubbles, and arbitrary stacking twist angles at the interface, this unclean physical splicing results in extremely weak interlayer coupling, making it impossible to induce charge redistribution and causing polarization degradation. This invention constructs a clean interface free of polymer contamination through in-situ liquid-phase epitaxy. (DFCHA)₂PbI₄ / MoS₂ epitaxial heterostructure, as shown... Figure 2 As shown, PFM testing recorded characteristic amplitude butterfly curves and clear 180° phase hysteresis loops. The epitaxial heterostructure exhibits phase hysteresis loops and amplitude butterfly curves in the out-of-plane direction, as observed in piezoelectric microscopy. The material possesses a reversible 180° phase loop even under zero DC bias, indicating that this epitaxial heterojunction exhibits reversible out-of-plane spontaneous polarization under zero DC bias, demonstrating novel out-of-plane ferroelectricity. Figure 3 The piezoelectric microscopy (PFM) scan of the epitaxial heterostructure in the out-of-plane direction further confirms that the material exhibits a significant out-of-plane piezoelectric amplitude response after the application of voltage, with an out-of-plane piezoelectric coefficient of 15 pm / V.

[0067] Example 2: The method differs from Example 1 in that, in step two, the van der Waals substrate with the reverse micelle solution dropped on it is transferred to a heating stage preheated to 140°C, resulting in a perovskite material heteroepitaxially grown on the van der Waals surface. An optical microscope image of the epitaxial heterostructure is attached. Figure 1 As shown in b, two-dimensional ferroelectric perovskite (DFCHA)2PbI4 was successfully grown on triangular MoS2 nanosheets.

[0068] Example 3: The method differs from Example 1 in that, in step two, the van der Waals substrate with the reverse micelle solution dropped on it is transferred to a heating stage preheated to 100°C, resulting in a perovskite material heteroepitaxially grown on the van der Waals surface. An optical microscope image of the epitaxial heterostructure is attached. Figure 1 As shown in Figure c, two-dimensional ferroelectric perovskite (DFCHA)2PbI4 was successfully grown on triangular MoS2 nanosheets.

[0069] Example 4: The method differs from Example 1 in that, in step one, the volume ratio of the precursor solution, octanoic acid, and chlorobenzene is 1:10:10, resulting in a perovskite material heteroepitaxially grown on a van der Waals surface. An optical microscope image of the epitaxial heterostructure is attached. Figure 1 As shown in d, two-dimensional ferroelectric perovskite (DFCHA)2PbI4 was successfully grown on triangular MoS2 nanosheets.

[0070] Example 5: The method differs from Example 1 in that, in step one, the volume ratio of the precursor solution, octanoic acid, and chlorobenzene is 1:15:10, resulting in a perovskite material heteroepitaxially grown on a van der Waals surface. An optical microscope image of the epitaxial heterostructure is attached. Figure 1 As shown in Figure e, two-dimensional ferroelectric perovskite (DFCHA)2PbI4 was successfully grown on triangular MoS2 nanosheets.

[0071] Example 6: The method differs from Example 1 in that, in step one, the volume ratio of the precursor solution, octanoic acid, and chlorobenzene is 1:25:10, resulting in a perovskite material heteroepitaxially grown on a van der Waals surface. An optical microscope image of the epitaxial heterostructure is attached. Figure 1 As shown in f, two-dimensional ferroelectric perovskite (DFCHA)2PbI4 was successfully grown on triangular MoS2 nanosheets.

[0072] Example 7: The method differs from Example 1 in that: in step one, 40.38 mg (0.2 mmol) of phenylethyl ammonium bromide (PEABr) powder and 36.70 mg (0.1 mmol) of lead bromide (PbBr2) powder are weighed and added together to a sample vial, dissolved in 1 mL of N,N-dimethylformamide (DMF) solvent to prepare a precursor solution with a molar concentration of (PEA)2PbBr4 of 0.1 mol / L; in step two, perovskite material heteroepitaxially grown on van der Waals surfaces is obtained, and optical microscope images of the epitaxial heterostructure are attached. Figure 4 As shown, two-dimensional nonferroelectric hybrid perovskite (PEA)2PbBr4 was successfully grown on triangular MoS2 nanosheets.

[0073] Example 8: The method differs from Example 1 in that: in step one, 30.78 mg (0.2 mmol) of n-butylammonium bromide (BABr) powder and 36.70 mg (0.1 mmol) of lead bromide (PbBr2) powder are weighed and added together to a sample vial, dissolved in 1 mL of N,N-dimethylformamide (DMF) solvent, and stirred until clear to prepare a precursor solution with a molar concentration of (BA)2PbBr4 of 0.1 mol / L; in step two, perovskite material heteroepitaxially grown on van der Waals surfaces is obtained, and optical microscope images of the epitaxial heterostructure are attached. Figure 5 As shown, a two-dimensional non-ferroelectric organic-inorganic hybrid perovskite (BA)2PbBr4, namely (BA)2PbBr4 / MoS2 van der Waals heterostructure, was successfully grown on a triangular MoS2 nanosheet.

[0074] Example 9: The method differs from Example 1 in that: in step one, 63.84 mg (0.3 mmol) of cesium bromide (CsBr) powder and 89.74 mg (0.2 mmol) of bismuth bromide (BiBr3) powder are weighed and added together to a sample vial, dissolved in 1 mL of N,N-dimethylformamide (DMF) solvent, and stirred thoroughly until completely dissolved to prepare a precursor solution with a molar concentration of 0.1 mol / L for Cs3Bi2Br9; in step two, perovskite material heteroepitaxially grown on van der Waals surfaces is obtained, and an optical microscope image of the epitaxial heterostructure is attached. Figure 6 As shown, inorganic lead-free perovskite Cs3Bi2Br9 was successfully grown on triangular MoS2 nanosheets.

[0075] Example 10: The method differs from Example 1 in that: in step one, 63.84 mg (0.3 mmol) of cesium bromide (CsBr) powder and 72.30 mg (0.2 mmol) of antimony bromide (SbBr3) powder are weighed and added together to a sample vial, dissolved in 1 mL of N,N-dimethylformamide (DMF) solvent, and stirred at a constant temperature until the solution is clear, thus preparing a precursor solution with a molar concentration of 0.1 mol / L for Cs3Sb2Br9; in step two, perovskite material heteroepitaxially grown on a van der Waals surface is obtained, and an optical microscope image of the epitaxial heterostructure is attached. Figure 7 As shown, inorganic lead-free perovskite Cs3Sb2Br9 was successfully grown on triangular MoS2 nanosheets.

[0076] Comparative Example 1: The method differs from Example 1 in that: in step one, a perovskite precursor solution with a molar concentration of (DFCHA)₂PbI₄ of 0.1 mol / mL was prepared; in step two, the 0.1 mol / mL perovskite precursor solution was directly spin-coated onto MoS₂, followed by growth at 120°C. Optical microscope images of the resulting material are attached. Figure 8 As shown, the result is that perovskite is grown non-epitaxetarily in solution and eventually falls randomly onto the substrate, rather than growing exclusively on MoS2. A comparison between Example 1 and Comparative Example 1 shows that the conventional spin-coating method, due to polarity mismatch, prevents the precursor from wetting the MoS2 surface, resulting in the formation of randomly shaped, disorderly arranged homogeneous aggregated crystals. Figure 1 As shown in the optical microscope image, after using the reverse micelle epitaxial growth method of the present invention, the perovskite material undergoes heterogeneous nucleation only on the triangular monolayer MoS2 nanosheets and grows into regular rectangular nanosheets. The rectangular nanosheets exhibit a specific orientation angle (the edges are parallel to MoS2). The present invention overcomes the wetting barrier, and the material crystallization is guided by the underlying van der Waals lattice, thus realizing heteroepitaxial growth.

[0077] Comparative Example 2: The method differs from Example 1 in that, in step two, perovskite crystals are grown by heating at 80°C without epitaxy. Optical microscope images of the resulting material are attached. Figure 9 As shown, the final growth occurs randomly on the substrate and does not only grow on MoS2.

[0078] Comparative Example 3: The method differs from that of Example 1 in that: in step two, the material is grown at 160°C, and an optical microscope image of the resulting material is attached. Figure 10 As shown, the high temperature causes the solvent to evaporate violently, causing the solute in the solution to precipitate and form irregular impurity crystals, which eventually fall randomly onto the substrate, making it impossible to grow perovskite.

[0079] Comparative Example 4: The method differs from that of Example 1 in that, in step one, the volume ratio of the precursor solution, octanoic acid, and chlorobenzene is 1:5:5. An optical microscope image of the resulting material is attached. Figure 11 As shown, a large number of perovskite crystals are grown non-epitaxially and eventually fall randomly onto the substrate, rather than growing only on MoS2.

[0080] Comparative Example 5: The method differs from that of Example 1 in that, in step one, the volume ratio of the precursor solution, octanoic acid, and chlorobenzene is 1:50:10. An optical microscope image of the resulting material is attached. Figure 12 As shown, excessive addition of surfactants results in too low a solute content, making it impossible to achieve perovskite growth, leaving only tiny crystals on the MoS2 surface.

[0081] The detailed descriptions listed above are merely specific illustrations of feasible embodiments of the present invention and are not intended to limit the scope of protection of the present invention. All equivalent embodiments or modifications made without departing from the spirit of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for heteroepitaxial growth of perovskite on a van der Waals surface, characterized in that, The method includes: Step 1: Dissolve the perovskite material in a strongly polar solvent with coordination ability to prepare a precursor solution. The perovskite material is a two-dimensional ferroelectric perovskite, a two-dimensional non-ferroelectric organic-inorganic hybrid perovskite, or an inorganic lead-free perovskite. Add a surfactant and a non-polar or weakly polar organic solvent that is affinity for the non-polar end of the surfactant to the precursor solution. After mixing evenly, a mixture is obtained. After centrifuging the mixture, the supernatant is collected to obtain a reverse micelle solution. Step 2: Take the reverse micelle solution obtained in Step 1 and drop it onto the van der Waals substrate and let it stand. Then heat the van der Waals substrate with the reverse micelle solution until the reverse micelle solution is completely dry to obtain a material with perovskite heteroepitaxially grown on the van der Waals surface.

2. The method for heteroepitaxial growth of perovskite on a van der Waals surface according to claim 1, characterized in that, The two-dimensional ferroelectric perovskite is (DFCHA)2PbI4, the two-dimensional non-ferroelectric organic-inorganic hybrid perovskite is (PEA)2PbBr4 and (BA)2PbBr4, and the inorganic lead-free perovskite is Cs3Bi2Br9 and Cs3Sb2Br9.

3. The method for heteroepitaxial growth of perovskite on a van der Waals surface according to claim 1, characterized in that, The molar concentration of perovskite material in the precursor solution is 0.02~0.1mol / L, and the volume ratio of the precursor solution, surfactant, and nonpolar or weakly polar organic solvent is 1:(10~30):

10.

4. The method for heteroepitaxial growth of perovskite on a van der Waals surface according to claim 1, characterized in that, The highly polar solvent with coordination ability is one or more of N,N-dimethylformamide, dimethyl sulfoxide, γ-butyrolactone, and N-methylpyrrolidone.

5. The method for heteroepitaxial growth of perovskite on a van der Waals surface according to claim 1, characterized in that, The surfactant is an amphiphilic organic carboxylic acid with a single-terminal carboxyl group and an aliphatic hydrocarbon chain.

6. The method for heteroepitaxial growth of perovskite on a van der Waals surface according to claim 1, characterized in that, The nonpolar or weakly polar organic solvent is one or more of chlorobenzene, toluene, xylene, chloroform, and n-hexane.

7. The method for heteroepitaxial growth of perovskite on a van der Waals surface according to claim 1, characterized in that, The van der Waals substrate is a SiO2 wafer with a single layer of MoS2. The method further includes: dissolving a molybdenum source and an alkaline modifier in a solvent to prepare a MoS2 precursor solution, spin-coating the MoS2 precursor solution onto a SiO2 / Si substrate, and then annealing it with sulfur powder in an argon atmosphere to obtain a SiO2 wafer with a single layer of MoS2.

8. The method for heteroepitaxial growth of perovskite on a van der Waals surface according to claim 1, characterized in that, In step two, the heating temperature is controlled to be 100~140℃.

9. A material for heteroepitaxial growth of perovskite on a van der Waals surface, characterized in that, The material is obtained by the method of heteroepitaxial growth of perovskite on a van der Waals surface as described in any one of claims 1 to 8.

10. An application of a material in which perovskite is heteroepitaxially grown on a van der Waals surface, characterized in that, This includes using the material described in claim 9, which is heteroepitaxially grown perovskite on a van der Waals surface, as a ferroelectric material or optoelectronic material.